2016
DOI: 10.1074/jbc.m116.732610
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Integrin α6 Recycling by Calcium-independent Phospholipase A2 (iPLA2) to Promote Microglia Chemotaxis on Laminin

Abstract: Microglia are the immune effector cells that are activated in response to pathological changes in the central nervous system. Microglial activation is accompanied by the alteration of integrin expression on the microglia surface. However, changes of integrin expression upon chemoattractant (ADP) stimulation still remain unknown. In this study, we investigated whether ADP induces the alteration of integrin species on the cell surface, leading to changes in chemotactic ability on different extracellular matrix p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It was further demonstrated that iPLA 2 activity is specifically required for the trafficking of c-Src back to the plasma membrane. Additional evidence for the important role of iPLA 2 in the regulation of microglia chemotaxis was from the study showing that the recycling of internalized α6 integrin vesicles and their delivery to focal adhesions also requires iPLA 2 activity during microglia chemotaxis ( Lee et al, 2016 ). Results from studies on chemotaxis of different types of cells clearly indicate that iPLA 2 takes a significant part in the regulation of chemotaxis.…”
Section: Microglial Chemotaxis and Its Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was further demonstrated that iPLA 2 activity is specifically required for the trafficking of c-Src back to the plasma membrane. Additional evidence for the important role of iPLA 2 in the regulation of microglia chemotaxis was from the study showing that the recycling of internalized α6 integrin vesicles and their delivery to focal adhesions also requires iPLA 2 activity during microglia chemotaxis ( Lee et al, 2016 ). Results from studies on chemotaxis of different types of cells clearly indicate that iPLA 2 takes a significant part in the regulation of chemotaxis.…”
Section: Microglial Chemotaxis and Its Regulationmentioning
confidence: 99%
“…The regulation of phosphorylation and dephosphorylation on VASP might be required for the membrane ruffle formation and growth of adhesion strength during membrane protrusion and retraction, exerting a direct impact on cell’s ability to chemotaxis ( Lee and Chung, 2009 ). It has been reported that ADP stimulation via P2Y 12 R induces the translocation of β1 and α6 integrins to the membrane ruffle regions ( Lee et al, 2016 ; Nasu-Tada et al, 2005 ). Redistribution of β1 was lost when the intracellular cAMP was increased, suggesting that PKA is a negative regulator of the β1 integrin translocation, resulting in a significant impact on microglia chemotaxis ( Nasu-Tada et al, 2005 ).…”
Section: Microglial Chemotaxis and Its Regulationmentioning
confidence: 99%
“…It was reported that the PLC-mediated increase in intracellular Ca 2+ concentration-triggered proteinkinase B (Akt) activation was also involved in the second-messenger mechanisms of P2Y12Rs [75]. Eventually, P2Y12Rs initiate an adhesive interaction with the surrounding extracellular matrix through integrins [76,77]. Nerve injury-activated microglia engulf myelinated axons in the spinal cord dorsal horn in a P2Y12R-triggered and p38 signaling-mediated manner; this reaction is causally involved in the pathogenesis of neuropathic pain [78,79].…”
Section: P2y12 Receptorsmentioning
confidence: 99%
“…We further examined whether CCBs could affect the interactions of BV-2 cells and extracellular matrix, which affects cell motility as well as a changes in capacitance, which were expected due to decrease in intracellular Ca 2+ and thus overall cell polarity when compared to the culture medium media. We utilized the electrical cell-impedance sensing (ECIS) system, as Lee et al reported the effective use of ECIS to detect the BV-2 cell migration activity by reading resistance as well as capable of resolving the capacitance [37]. Due to the low sensitivity of the ECIS device, we used higher concentrations of the respective substances (10 μM) in the short-term experiment of 4 h. The ECIS results demonstrated a rapid decrease in the resistance at 4 kHz ( Fig.…”
Section: In Vitro Toxicity Efficacy and Dose-response Evaluation Ofmentioning
confidence: 99%